2000
DOI: 10.1001/archinte.160.12.1749
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients With Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is a frequent and costly health care problem. In patients with AF, the restoration and maintenance of sinus rhythm is the primary therapeutic goal. The most frequent strategy for maintaining sinus rhythm after restoration is the use of antiarrhythmic drugs. The efficacy of therapy in AF has been predominantly measured using objective criteria such as mortality and morbidity. In recent years, the importance of quality of life (QoL) as an outcome measure has been recognized. However, few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 30 publications
0
56
0
6
Order By: Relevance
“…4 AF is also associated with other embolic events and reduced quality of life. 26,27 Even when AF is diagnosed and treated, the antiarrhythmic and antithrombotic medications required to prevent recurrences or for prophylaxis against embolic phenomena carry their own attendant risks. 28 -30 Recent large clinical trials (RACE 29 and AFFIRM [Atrial Fibrillation Follow-up Investigation of Rhythm Management] 30 ) suggest that strategies designed to maintain sinus rhythm do not improve survival compared with rate control and anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…4 AF is also associated with other embolic events and reduced quality of life. 26,27 Even when AF is diagnosed and treated, the antiarrhythmic and antithrombotic medications required to prevent recurrences or for prophylaxis against embolic phenomena carry their own attendant risks. 28 -30 Recent large clinical trials (RACE 29 and AFFIRM [Atrial Fibrillation Follow-up Investigation of Rhythm Management] 30 ) suggest that strategies designed to maintain sinus rhythm do not improve survival compared with rate control and anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Early studies, which suggested that AF had substantial effects on QOL, akin to other chronic diseases such as coronary artery disease or HF, were often limited by small size, design, or the use of nonvalidated instruments. 17,19 Studies in highly symptomatic patients with AF undergoing atrioventricular node ablation and often subsequent pacemaker placement also reported marked improvement in QOL in these selected patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Early studies, which suggested that AF had substantial effects on QOL, akin to other chronic diseases such as coronary artery disease or HF, were often limited by small size, design, or the use of nonvalidated instruments. 17,19 Studies in highly symptomatic patients with AF undergoing atrioventricular node ablation and often subsequent pacemaker placement also reported marked improvement in QOL in these selected patient populations. [20][21][22][23] However, in the older, less selected population enrolled in the AFFIRM QOL substudy, QOL was comparable between rate and rhythm control strategies and was also similar in SR versus AF, 24,25 suggesting that effects on QOL associated with AF were quite modest in an older, medically managed population.…”
Section: Discussionmentioning
confidence: 99%
“…In eight of these studies, we found argument for measuring QOL or health-related QOL, referring to SF-36 as the most valid and widely applied tool [27,35,46,53,54,61,75,76]. In six of the papers [4,28,33,36,46,57], QOL or health-related QOL was defined as a multidimensional concept with subjective elements which was hard to assess and use as outcome in clinical trials. Furthermore, these papers also emphasised the importance and difficulties in working with the concept.…”
Section: The Text Close Analysis Levelmentioning
confidence: 99%